The intermediate Accounting series : Volume 1 - Robles, Nenita S.; Empleo, Patricia M. (Mandaluyong city, 2016)
?The Intermediate Accounting Series: Volume 1, authored by Patricia M. Empleo and Nenita S. Robles, is a comprehensive textbook designed for students and professionals aiming to deepen their understanding of financial accounting principles. This volume covers foundational topics such as the development of the accounting profession, the accounting process, and detailed discussions on financial statements, including the Statement of Financial Position, Statement of Comprehensive Income, and Statement of Cash Flows. It emphasizes both theoretical frameworks and practical applications, providing readers with the knowledge necessary to prepare and analyze financial information effectively. The book also includes exercises and problems to reinforce learning and facilitate mastery of intermediate accounting concepts.
Keywords: Accounting